DNA double‐strand breaks as a method of radiation measurements for therapeutic beams - Obeidat, Mohammad (Med Phys, 2018)
PURPOSE: Many types of dosimeters are used to measure radiation dose and calibrate radiotherapy equipment, but none directly measure the biological effect of this dose. The purpose here is to create a dosimeter that can measure the probability of double‐strand breaks (DSB) for DNA, which is directly related to the biological effect of radiation. METHODS: A DNA dosimeter, consisting of magnetic streptavidin beads attached to four kilobase pair DNA strands labeled with biotin and fluorescein amidite (FAM) on opposing ends, was suspended in phosphate‐buffered saline (PBS). Fifty microliter samples were placed in plastic tubes inside a water tank setup and irradiated at the dose levels of 25, 50, 100, 150, and 200 Gy. After irradiation, the dosimeters were mechanically separated into beads (intact DNA) and supernatant (broken DNA/FAM) using a magnet. The fluorescence was read and the probability of DSB was calculated. This DNA dosimeter response was benchmarked against a Southern blot analysis technique for the measurement of DSB probability. RESULTS: For the DNA dosimeter, the probabilities of DSB at the dose levels of 25, 50, 100, 150, and 200 Gy were 0.043, 0.081, 0.149, 0.196, and 0.242, respectively, and the standard errors of the mean were 0.002, 0.003, 0.006, 0.005, and 0.011, respectively. For the Southern blot method, the probabilities of DSB at the dose levels of 25, 50, 100, 150, and 200 Gy were 0.053, 0.105, 0.198, 0.235, and 0.264, respectively, and the standard errors of the mean were 0.013, 0.024, 0.040, 0.044, and 0.063, respectively. CONCLUSIONS: A DNA dosimeter can accurately determine the probability of DNA double‐strand break (DSB), one of the most toxic effects of radiotherapy, for absorbed radiation doses from 25 to 200 Gy. This is an important step in demonstrating the viability of DNA dosimeters as a measurement technique for radiation.